A facility for measurements of nuclear cross sections for fast neutron cancer therapy - Dangtip, S; Ataç, A; Bergenwall, B; Blomgren, J; Elmgren, K; Johansson, C; Klug, J; Olsson, N; Carlsson, G.Alm; Söderberg, J; Jonsson, O; Nilsson, L; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2000)
A facility for measurements of neutron-induced double-differential light-ion production cross-sections, for application within, e.g., fast neutron cancer therapy, is described. The central detection elements are three-detector telescopes consisting of two silicon detectors and a CsI crystal. Use of Δ E–Δ E– E techniques allows good particle identification for p, d, t, 3He and alpha particles over an energy range from a few MeV up to 100 MeV. Active plastic scintillator collimators are used to define the telescope solid angle. Measurements can be performed using up to eight telescopes at 20° intervals simultaneously, thus covering a wide angular range. The performance of the equipment is illustrated using experimental data taken with a carbon target at E n=95 MeV. Distortions of the measured charged-particle spectra due to energy and particle losses in the target are corrected using a newly developed computer code. Results from such correction calculations are presented.